2023
DOI: 10.1155/2023/6917910
|View full text |Cite
|
Sign up to set email alerts
|

Stability Evaluation of Sliding-Type Perilous Rock in Huangzangsi Hydrojunction Project Based on Natural Vibration Frequency

Abstract: The instability of perilous rock is mostly manifested as sudden collapse and failure without obvious displacement characteristics. Therefore, it is difficult to achieve the purpose of monitoring and early warning by conventional displacement monitoring. But the existing stability monitoring indicators are mostly deformation, stress, and strain. There is a problem that the stability evaluation parameters are inconsistent with the monitoring parameters. Taking sliding-type perilous rock as the research object, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Among others, Song et al (2019a) investigated the effects of natural frequencies on the slope dynamic characteristics, and they concluded that the high-and low-frequency components mainly induce local and overall deformation of the surface slope of the rock, respectively. In order to achieve the stability evaluation of the perilous rock, Jia et al (2023aJia et al ( , 2022 found that the natural frequency increases nonlinearly in the horizontal direction with the increasing buried depth of the unstable rock, and they established the quantitative relationship model between the safety factor and natural frequency. Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Song et al (2019a) investigated the effects of natural frequencies on the slope dynamic characteristics, and they concluded that the high-and low-frequency components mainly induce local and overall deformation of the surface slope of the rock, respectively. In order to achieve the stability evaluation of the perilous rock, Jia et al (2023aJia et al ( , 2022 found that the natural frequency increases nonlinearly in the horizontal direction with the increasing buried depth of the unstable rock, and they established the quantitative relationship model between the safety factor and natural frequency. Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Du Yan [21] and other rock mass collapse disaster early warning ideas based on the identification of damage precursors in the separation stage have obtained an early monitoring and early warning index system based on a trinity of dynamic indicators, static indicators, and environmental quantity indicators. Jia Yanchang [22] and others calculated the bonding area between the perilous rock block and the parent rock by real-time monitoring of the natural vibration frequency of the perilous rock block and realized its stability accurately and quickly. Zhao Chen [23] and others introduced the concept of mutual approximation entropy and extended it to three dimensions, and realized the quantitative analysis of particle trajectories, which provided a new research idea for the early warning of perilous rock damage identification and collapse.…”
Section: Introductionmentioning
confidence: 99%